Islamic finance a comparative jurisprudential study - Elsefy, Hossam (University Malaya Press, 2007)
This book is devoted to an essential concept in modern economic theory in Islamic finance that is concept of guarantee which inculcates the sense of confidence and safe in many commercial transactions. Indeed this concept is far more developed in Islamic law compared with any other legal systems as it was put in practice for many year.